(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Purple rice is an unidentified rice cultivar that has purple colour leaf. Some farmers of Bangladesh are showing interest to cultivate purple rice due to its ornamental look and high price of seeds. Hence, before occupying the green rice land by the purple rice, more information about purple rice is necessary to guide farmers properly. Less information about purple rice is available in any area of research except nutritional analysis. Purple rice leaf has high antioxidant properties which play role in stress tolerance. The salt-stress tolerance potentiality of purple rice compared to green rice has been reported. Therefore, as a part of unraveling the heavy-metal stress tolerance potentiality of purple rice, here, we aimed to find out the arsenic-stress tolerance potentiality of purple rice. Arsenic is a toxic metalloid that disrupts plant cells. The effects of different arsenate concentrations (e.g. 0 µM, 100 µM, and 500 µM) on purple rice and BRRI dhan28 were observed based on morpho-biochemical parameters. The results of purple rice were compared with those of green rice (BRRI dhan28). Arsenic stress reduced root length and plant height compared to control in both rice but the reductions in purple rice were lesser than those of BRRI dhan28. Proline, a compatible solute, content was higher in purple rice under both arsenic stress and non-stress conditions compared with BRRI dhan28 and the proline content was decreased in BRRI dhan28 in a concentration-dependent manner. The catalase (an antioxidant enzyme) activity was increased in both rice under arsenic stress conditions compared to control and purple rice showed more activity than BRRI dhan28 in response to arsenic stress. Arsenic stress increased the anthocyanin content (a purple-colored leaf pigment) in a concentration-dependent manner in purple rice than that of BRRI dhan28. BRRI dhan28 showed reduction of chlorophyll and carotenoid contents under arsenic stress compared to the both control and purple rice. The ability of less reduction of phenotypes in purple rice might be achieved by the higher activity of catalase and a higher level of anthocyanin content. Though proline is utilized in BRRI dhan28 under arsenic stress it was either just a symptom or influenced the antioxidant homeostasis without decreasing its concentration. Purple rice may have more potential to protect its cell reductions by arsenic stress than BRRI dhan28. J Bangladesh Agril Univ 22(4): 451–459, 2024